Probiotic active gel promotes diabetic wound healing through continuous local glucose consumption and antioxidant - Yingshuai Wang; Lihua Shi; Junna Lu; Fengyuan Wang; Zihan Zhou; Yuexuan Wang; Xiangyu Du; Di Qin; Fangman Chen; Dan Shao; Yuanyuan Gao; Cheng Gao; et al. (Journal of Nanobiotechnology)
Abstract Background Diabetic foot ulcers (DFU) are severe complications of diabetes, posing significant health and societal challenges. Accumulation of reactive oxygen species (ROS) and elevated glucose levels are primary factors affecting diabetic wound healing. Achieving effective treatment by reducing ROS alone is challenging, as high glucose levels continuously drive ROS production. The excellent glucose-consuming capacity of lactobacilli and the antioxidant function of hydrogen undoubtedly provide good therapeutic ideas. Herein, we combined probiotic Lactobacillus reuteri with acid-responsive hydrogen-producing nanoparticles to construct probiotic active gel LR&AB@CAH to enable a cascade of glucose consumption and hydrogen production. Lactobacillus reuteri consumed overproduced glucose and thereby released lactic acid to activate nanoparticle for hydrogen production, which could neutralize excess ROS and promote wound healing. Results In vitro experiments demonstrate that LR&AB@CAH has good biocompatibility, antioxidant capacity. LR&AB@CAH reduces excess ROS, decreases oxidative substances, and boosts antioxidant enzyme activity. In a diabetic wound mouse model, it functions as a glucose scavenger and antioxidant, reducing ROS and supporting wound healing. Conclusion LR&AB@CAH offers a novel strategy for the comprehensive treatment of DFU. This study provides an artificial-natural composite hydrogel for cascade therapy on diabetic wound healing, and suggests a complete management approach for diabetic oxidative stress.